2015
DOI: 10.4236/ojst.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Morphometry of the Lingual Nerve in Relation to the Mandibular Third Molar

Abstract: The position and branching of the lingual nerve (LN) in the mandibular third molar region were documented in 30 head hemi-sections (16: right and 14: left). In all the dissections, the LN was found below the level of the posterior alveolar crest (PAC). Branching was observed in 26 (86.7%) of the 30 specimen in which one branch was most frequently given per hemi-section. All branches were located superior to the main trunk of the LN. The mean vertical distance of the LN from the PAC was 10.3 ± 5.2 mm (range: 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Interestingly the less common site is at the retromolar pad region, which was noticed in 0.15 and 1.5% of the cases [ 11 , 13 ]. When not in contact with the lingual plate, the LN usually lies within 2.28–16.8 mm below the alveolar crest and 0.57–7.10 mm medial from the lingual plate [ 6 , 11 , 17 ]. Trost et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly the less common site is at the retromolar pad region, which was noticed in 0.15 and 1.5% of the cases [ 11 , 13 ]. When not in contact with the lingual plate, the LN usually lies within 2.28–16.8 mm below the alveolar crest and 0.57–7.10 mm medial from the lingual plate [ 6 , 11 , 17 ]. Trost et al .…”
Section: Introductionmentioning
confidence: 99%
“…The LN may give off a branch to the lingual gingival tissue, extending horizontally from the medial mandibular cortex at the level of the retromolar pad to mesial of the lower first molars-second premolars to supply the lingual periosteum, gingiva, and mucosa that are overlying the medial alveolar process [ 7 , 17 , 19 , 20 ]. Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the studies were found to be of a low risk of bias for Domains 2, 4, and 5. For Domain 1, 66.7% of studies had a high risk of bias due to incomplete reporting of the subject ages, ethnicity, and sex 19 , 24 , 27 - 33 , 35 , 36 . For Domain 3, 11 studies were found to have a high risk of bias due to inadequate reporting of methodological details required for replicating the study or the lack of examiner calibration or alignment 22 - 24 , 27 - 30 , 32 , 33 , 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…En cuanto a la inervación del piso de la boca, la proyección del tronco nervioso mandibular del nervio trigémino, de esa división mandibular se originan numerosos filetes nerviosos: el nervio lingual (Al-Amery et al, 2016) y el nervio alveolar inferior según lo menciona Wolf et al (2016) o también conocido como nervio dentario inferior según lo describe Bokindo et al (2015). El nervio alveolar inferior se dirige hacia abajo y adelante, ingresa por el foramen de la mandíbula y atraviesa internamente el canal de la mandíbula dando inervación a los dientes a nivel de la pulpa (Wolf et al, 2016); sin embargo, antes de ingresar a la mandíbula, emite un delgado nervio, que es el milohioideo, el cual proporciona inervación al músculo milohioideo (Wolf et al, 2016;Bokindo et al, 2015). Este nervio discurre paralelo al músculo milohioideo, dando ramificaciones para inervación motora al milohioideo y al vientre anterior de los músculos digástricos, aunque casi siempre se menciona que el nervio milohioideo es un nervio motor (Bokindo et al, 2015).…”
Section: Inervación E Irrigaciónunclassified
“…El nervio alveolar inferior se dirige hacia abajo y adelante, ingresa por el foramen de la mandíbula y atraviesa internamente el canal de la mandíbula dando inervación a los dientes a nivel de la pulpa (Wolf et al, 2016); sin embargo, antes de ingresar a la mandíbula, emite un delgado nervio, que es el milohioideo, el cual proporciona inervación al músculo milohioideo (Wolf et al, 2016;Bokindo et al, 2015). Este nervio discurre paralelo al músculo milohioideo, dando ramificaciones para inervación motora al milohioideo y al vientre anterior de los músculos digástricos, aunque casi siempre se menciona que el nervio milohioideo es un nervio motor (Bokindo et al, 2015). Iwanaga et al (2019), postula que podría estar involucrado en la inervación sensorial a nivel medial de la mandíbula en el 43-60 % de la población; así mismo, Vasconcellos et al (2009), plantea que también estaría involucrado en la inervación accesoria para los dientes inferiores.…”
Section: Inervación E Irrigaciónunclassified